PENGEMBANGAN AQIDAH AKHLAK PADA ANAK USIA DINI MELALUI METODE MODELING - Nuryati Nuryati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2018)
This article describes the development of Aqidah Akhlak in early childhood through the modeling method at RA Nurul Ikhlas Taktakan Serang. The role of teachers in developing Akidah Morals on learning activities, as well as the role of parents and society. This research is qualitative research of phenomenology in group B in RA Nurul Ikhlas Legok Widara Taktakan Serang year 2017. Data analysis technique using Miles and Huberman model consists of: data reduction, data display, and verification. Data collection techniques are observation, interview and documentation. The results showed that the moral character of children in RA Nurul Ikhlas is very good, with the method applied in the school, that is by using the modeling method. This can be seen by the existence of good behavior that shows the child in his daily life both at school and at home. The role of teachers in developing Akidah Akhlak in early childhood can be done through the modeling method that is done every day at school by the teacher, and with the cooperation with parents.